Evaluation of Madidihang Fishery (Thunnus Albacares) Management Based on Ecosystem in Ternate City Waters (Case Study based at PPN Ternate) - M. Abdullah, Rommy; Kamaruddin, Kamaruddin; Sulfiarini, Sulfiarini; Kurniawan, Edi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
Yellowfin tuna is one of the fishery export commodities which have important economic value. The rapid development of tuna exporting companies in North Maluku with raw materials from fishermen's catch has resulted in an increase in the frequency of fishing, so there is concern that it will have an impact on reducing tuna stocks. In the last three years, the volume of yellowfin tuna landed at PPN Ternate has decreased. This is not only caused by the increasing number of tuna fishing fleets, but also presumably by fishing which is generally pre-maturity. The purpose of this study was to analyze the current state of yellowfin fishery management through an ecosystem approach in the waters of Ternate city. The method used is descriptive method with flag modeling analysis. The results showed that the mean composite value of the entire domain was obtained at 70.19, which reflects a good status in applying EAFM principles. Indicators that become priority in yellowfin fishery management using an ecosystem approach are the proportion of juvenile fish caught and fish resource range collapse (SDI domain); status of mangrove ecosystems (habitat and ecosystem domains); fishery capacity (fishing technique domain); savings ratio (economic domain); stakeholder participation and fisheries conflicts (social domain); and adherence to fisheries principles responsible for fisheries management that have been formally and informally established (institutional domain).